Higher Levels of Hair Ethyl Glucuronide in Patients with Decreased Kidney Function. (14th June 2012) - Høiseth, Gudrun; Morini, Luca; Ganss, Rudiger; Nordal, Kristin; Mørland, Jørg
Abstract : Background: Hair levels of ethyl glucuronide (EtG) are often used to differentiate social drinking from heavy drinking. Patients with decreased kidney function have delayed excretion of EtG, and increased incorporation into hair could be suspected. The aim of this study was to compare hair EtG levels in patients with decreased kidney function to those seen in healthy volunteers. Methods: Twelve patients with renal disease were included. The levels of EtG in hair were adjusted to estimated daily intake of ethanol (EDI) and compared to 21 previously published healthy individuals. Results: The levels of hair EtG in the 12 patients ranged between < limit of detection and 134 pg/mg, and the EDI ranged between 0.1 and 12 g. The levels of EtG in hair were significantly higher in the patients compared to healthy volunteers ( p = 0.009). Conclusions: These preliminary results indicate that hair levels of EtG in a population of patients with decreased kidney function should be interpreted with caution.